Sensitization to the prosocial effects of 3, 4-methylenedioxymethamphetamine (MDMA). (June 2019) - Curry, Daniel W.; Berro, Laís F.; Belkoff, Andie R.; Sulima, Agnieszka; Rice, Kenner C.; Howell, Leonard L.
Abstract: The recreational drug 3, 4-methylenedioxymethamphetamine (MDMA) has well documented prosocial effects and is currently under clinical investigation as a treatment for patients with PTSD, autism, and other conditions. Early clinical trials have found that MDMA-assisted therapy may have robust long-lasting therapeutic effects, yet the mechanism by which acute treatments produce these long-term effects is unclear. Sensitization to certain behavioral drug effects is a common rodent model used to assess long-lasting neurobiological adaptations induced by acute drug treatments. Nine independent experiments were undertaken to investigate if and how mice sensitize to the prosocial effects of MDMA. When treated with 7.8 mg/kg MDMA and paired every other day for a week, MDMA-induced social interaction increased precipitously across treatment sessions. This previously unreported phenomenon was investigated and found to be heavily influenced by a social context and 5-HT2A R activation. Social sensitization did not appear to develop if mice were administered MDMA in isolation, and pretreatment with MDL100907, a selective 5-HT2A R antagonist, inhibited the development of social sensitization. However, when MDL100907 was administered to mice that had already been sensitized, it did not attenuate social interaction, suggesting that 5-HT2A R activity may be necessary for the development of social sensitization but not the expression of MDMA-induced social behavior. Additional investigation is warranted to further explore the phenomenon of social sensitization and to determine the underlying neurobiological mechanisms. Highlights: Mice sensitize to the prosocial effects of MDMA. A social context during MDMA treatment was critical for the development of social sensitization. Pretreatment with a 5-HT2A R antagonist inhibited the development of social sensitization.